1976
DOI: 10.1111/j.2042-7158.1976.tb04648.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of neuroleptic drugs on dopamine turnover in the extrapyramidal and limbic system

Abstract: In gallamine-immobilized cats, the caudate nucleus and the nucleus accumbens septi were perfused by means of a push-pull cannula and dopamine was measured in the perfusate. Chlorpromazine (10 mg kg(-1)) and clozapine (20 mg kg(-1)), administered intravenously, enhanced the release of dopamine. The effect of chlorpromazine was similar in both regions whereas that of clozapine was more pronounced in the nucleus accumbens than in the caudate nucleus. Furthermore, in the rat, sulpiride, clozapine and thioridazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…The anti-dopamine character of sulpiride in the central nervous system has been described in many reports (1,(17)(18)(19)(20)(21)(22)(23). However, the drug was reported not to block the dopamine-sensitive adenylate cyclase (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-dopamine character of sulpiride in the central nervous system has been described in many reports (1,(17)(18)(19)(20)(21)(22)(23). However, the drug was reported not to block the dopamine-sensitive adenylate cyclase (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also point to an interaction with some ionotropic receptors, for example, the N-methyl-D-aspartate (NMDA) receptor (Arvanov et al, 1997;Ossowska et al, 1999) and the GABA A receptor (Squires and Saederup, 1998). It has been suggested that clozapine has a preferential action on the mesolimbic DA system as compared to the nigrostriatal DA system (Andén and Stock, 1973;Bartholini, 1976;Bunney, 1983, 1985;Moghaddam and Bunney, 1990). Moreover, since clozapine is a potent serotonin 5-HT 2 -receptor antagonist, it has been suggested that concurrent 5-HT 2 and DA-D 2 receptor antagonism may contribute to its atypical profile (see Deutch et al, 1991;Ichikawa et al, 2001;Meltzer and Nash, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…There may also be a variety of regional differences in the microenvironment surrounding the receptor-enzyme complex, such as the presence or absence within the membranes of certain neuroregulators that interact with the adenylate cyclase system. Dopamine turnover in the mesolimbic terminal region has been shown to differ from striatum in response to short-or long-term treatment with neuroleptics (e.g., Bartholini, 1976;Kaneno et al, 1978;Scatton et al, 1977). Moreover, basal rates of dopamine synthesis and metabolism are quite different in these 2 brain regions.…”
Section: Discussionmentioning
confidence: 99%